Comparison of the effect of three intramuscular sedation protocols on packed cell volume and total protein in cats. Issue 12 (December 2022) - Skelding, Alicia M; Valverde, Alexander
Objectives: The aim of this study was to evaluate the change in packed cell volume (PCV) and total protein following intramuscular preanesthetic sedation with one of three drug combinations in cats. Methods: Thirty client-owned cats were enrolled in this prospective, randomized, blinded, clinical study. A venous blood sample was obtained prior to administration of any sedation and PCV, total protein, electrolytes (Na +, K +, Cl –, iCa 2+ ), glucose and lactate were measured. Cats were randomly assigned to receive one of three intramuscular sedation protocols (n = 10 cats/protocol): methadone 0.2 mg/kg + acepromazine 0.02 mg/kg (MA), methadone 0.2 mg/kg + dexmedetomidine 5 µg/kg (MD) or methadone 0.2 mg/kg + midazolam 0.2 mg/kg + alfaxalone 2 mg/kg (MMA). Twenty-five minutes later, cats were assessed for level of sedation followed by another venous blood sampling to evaluate the same variables as above. Results: There were no significant differences in demographics (age, weight, sex) between groups. Level of sedation was significantly higher in MMA cats. Within groups, after premedication, PCV and hemoglobin significantly decreased in all groups, total protein significantly decreased in the MA and MMA groups and glucose significantly increased in the MD group. For electrolytes, statistical changes were not clinically relevant; Cl – mean difference was significantly different between MA and MD; in the MD group Na + and Cl – significantly decreased and in the MMA group Cl – significantly increased. Conclusions and relevance: All three sedation protocols caused significant decreases in PCV and hemoglobin in healthy cats.